FRI0189 Comparison of Gene-Expression Modification Profiles Between Targeting IL-6 and Targeting Jak Treatment: Effecting Common Biological Processes or Disparate?. (9th June 2015) - Koyama, Y.; Numata, K.; Nakamura, S.; Nagano, S.; Ota, T.; Higuchi, T.
Abstract : Background: Tofacitinib (TOF) is the selective kinase inhibitor to be approved to treat rheumatoid arthritis (RA). TOF inhibits Janus kinase (JAK) 1, JAK3 and, to a lesser extent, JAK2, which is known to lead inhibition of cytokine signaling including interleukin (IL)-6. Tocilizumab (TCZ), an anti-IL6 receptor monoclonal antibody, also block IL-6 signaling by preventing IL-6 from binding to both membrane-bound and soluble receptors. Although the targets of these treatments are specific, the downstream biological activities seem to be wide. Objectives: To investigate whether the effect of TOF and TCZ treatments share common biological process or are disparate Methods: Total of 29 RA cases were analyzed, including TOF (n=15: 6-20mg/d) and TCZ (n=10: 8mg/kg/4w) treatment groups. Peripheral blood was drawn at just before (pre) and 3 months after (post) these treatments. Total RNAs were then extracted with PAXgene miRNA kit. After constructing single-stranded, strand-specific libraries, multiplex sequencing was done. After quantifying the expressions of transcripts, differentially expressed genes (DEGs) of the good/moderate responder by EULAR response criteria were selected by paired comparison (post vs. pre), setting thresholds at 2-fold change up/down and less than P=0.05 in paired T-test. And then, hierarchical clustering analysis and enrichment analysis using gene ontology (GO) terms were performed. Next, alterations in gene-expression of the biomarkers included in "Vectra® DA" or "Bio-Plex® cytokine, chemokine, and growth factor assays" were investigated. Results: The 12 of 15 cases in TOF and the 8 of 10 cases in TCZ were selected as responders who met good or moderate response criteria after the treatments. In total, 57571 genes/transcripts including 976 newly predicted genes were quantified. The 149 and 419 genes, including overlapped 10 genes, were selected as DEGs from responders in TOF and TCZ group, respectively. By a hierarchical clustering analysis with using these DEGs, the TOF and TCZ treatment cases were segregated each other. By enrichment analysis, GO terms relevant to defense response to virus were dominant in the down-regulated DEGs of the TOF group, whereas terms related to wound healing or platelet function were enriched in the down-regulated DEGs of the TCZ group. The directions of alteration in gene-expression of four biomarkers included in "Vectra® DA" or "Bio-Plex®" by these treatments were found to be opposite to each other. The TOF-up/TCZ-down was resistin, while TOF-down/TCZ-up was IL-15, IL-2 receptor alpha (IL-2Rα) and vascular endothelial growth factor A (VEGFA). Conclusions: The influence of TOF or TCZ treatment over the transcriptome in the peripheral blood seems to be disparate. Enrichment analysis using GO terms suggests that particular attention should be given to viral infection during TOF treatment, and that wound healing might be delayed by TCZ treatment. After the favorable response by TOF or TCZ treatment, the directions of gene-regulation for some of biomarkers including resistin and VEGFA were opposite between these two treatments. It is noteworthy that these biomarkers were known to be important for evaluating RA disease activity. These observations may propose a rationale for selecting an optimal treatment for each RA patient. Disclosure of Interest: Y. Koyama Grant/research support from: Daiichi Sankyo Inc., Eli Lilly Japan Inc, K. Numata: None declared, S. Nakamura: None declared, S. Nagano: None declared, T. Ota: None declared, T. Higuchi: None declared